PERENCANAAN BISNIS INDUSTRI TEPUNG GLUKOMANAN PORANG (Amorphophallus oncophyllus): Industrial Planning of Porang Glucomannan Flour (Amorphophallus oncophyllus) - Kevin Tanjung; Didik Purwadi; Eni Harmayani (Universitas Darussalam Gontor, 2022)
The Cultivation and production of Porang in Indonesia are abundant. however, most of the results are exports, Porang should be used alone to make glucomannan flour. The output of glucomannan flour in Indonesia is still in the development stage, and most of it is still on a laboratory scale to develop Porang. Glucomannan flour is to increase the scale of production to be more significant. This study analyzes whether the glucomannan flour industry is technically, financially, and marketing feasible if established in Indonesia. The results showed that from a technical and technological perspective, the production process of porang tubers to become glucomannan flour was feasible because there were already standards for equipment, material use, and production at a laboratory scale. Financial analysis will be viable if the IRR, NPV, PI, and PP calculation results meet their respective criteria. Market and marketing analysis are feasible if a product has an opportunity for its market. The market and marketing analysis using the STP method shows that glucomannan flour can use segmenting to be developed into targeting, which then gets the product's image by positioning.